MANAJEMEN PENDIDIKAN KARAKTER DI MADRASAH - Ahmad Salim (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2015)
The existence of inequality of educational outcomes in terms of the behavior of graduates like brawl, corruption, free sex, drug, theft and other deviant behavior. Even some immoral allegedly perpetrated by